The Appropriation of the Arts: Folk Song in Advertising, Film, and Beyond - Fernando, Henky; Larasati, Yuniar Galuh; Suryati Suryati; RM Singgih Sanjaya (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2025)
The use of traditional musical elements in production and consumption activities significantly impacts the formation of appropriation of musical artworks. However, this topic remains underexplored in scholarly discussions. In response to gaps in previous studies, this research focuses on the characteristics of production and consumption activities that adopt elements and elements of traditional music to analyze the potential for appropriation of musical artworks. Employing a qualitative descriptive approach rooted in case analysis, this study highlights that the use of elements of traditional music adopted into production and consumption activities has significant effects on the formation of appropriation of musical artworks because it has degraded the appreciation of the essence and function of musical artwork. This study contributes to evaluating the influence of the adoption of musical artworks on the essence and existence of traditional music to address fundamental issues that have the potential to degrade the values of appreciation for the essence and function of musical artwork.